University Teachers’ Motivation and Challenges: A Gender Perspective on Professional Development - Pageni, Sakuntala (Prithvi Journal of Research and Innovation, 2021)
This article has attempted to explore motivation for female teachers in the classroom and to find out the affecting factors in the process of becoming a successful teacher in the university. This study is theoretically based on motivation theory and critical theory. The female teachers' professional challenges have persisted for many years. In this study, motivation for the female teachers and their challenges that focus on the participation of all strata of gender, race, ethnicity and other aspects are two sides of teachers’ professional identity. Therefore, motivation for female teachers in higher education is an urgent need for improving teaching and learning environment and for job security. This article includes a narrative inquiry based on an in-depth interview that includes three female teachers of the university. The thematic content analysis of this study is based on primary sources of data and theoretical observations. This study concludes that the female participation in higher education in Nepal is satisfactory, but they have not been able to improve their situation though they are capable of encouraging motivation for students to learn and face challenges in higher education.